DEVELOPING FUTURE CYBERSECURITY PROFESSIONALS’ SOFT SKILLS THROUGH BUSINESS ENGLISH CLASSES - Konoplianyk, Lesia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article deals with the distinctive aspects of developing 21st-century skills for future cybersecurity professionals while learning a Business English course. These skills empower them to interact effectively with peers and other professionals, address challenges and make decisions, all of which are crucial in the field of cybersecurity. The purpose of the study was to underscore the significance of soft skills for future cybersecurity professionals and offer practical advice on their development in Business English classes. The study involved implementing specific tasks, including determining the list of soft skills relevant to the professional activities of future cybersecurity professionals and identifying soft skills developed during Business English classes, as well as elaborating assignments that would contribute to their development. Theoretical, general scientific, and empirical methods were employed during the research, which took place at the National Aviation University and involved Master’s degree students majoring in “Cybersecurity”. Result. Upon conducting the analysis of methodological literature and regulatory documents (the Standard of Higher Education for “Cybersecurity” at the second (master’s) level, educational and professional programs and syllabi), the study examined the process of cultivationg future cybersecurity professionals’ soft skills during their study of Business English. The analysis led to the compilation of the list of soft skills that are developed during the classes, including practical application of the acquired knowledge, research skills, analytical abilities, abstract thinking, critical thinking, communication skills for networking with diverse professional groups, and teamwork skills. The author illustrated tasks and gave recommendations on effective forms and methods for developing and improving these skills, such as the case method, role-plays, the project method, discussions, debates, etc). The study explored how the incorporation of these soft skills enhances collaboration and efficiency in the area of cybersecurity and highlighted their role in fostering critical thinking and analytical skills crucial for identifying and addressing cyber threats. Conclusions. It is worth noting that tasks designed for developing soft skills during Business English classes contribute not only to the improvement of communication and teamwork skills but also to the development of abstract thinking and critical analysis. These skills are vital for successful professional activities in the field of cybersecurity. This emphasizes the importance of soft skills development in higher education across disciplines ensuring the readiness of future professionals to meet the challenges of the modern information environment